LEGAL PROTECTION OF VICTIMS – RIGHTS IN SEXUAL ABUSE CASES OF CHILDREN: (CASE STUDY OF DECISION NUMBER 1607/Pid.Sus/2021/PN. Tjg) - Wayan Maliastra (PRANATA HUKUM, 2023)
This study aims to determine the legal protection of victims' rights in cases of sexual abuse of children. That is special treatment in the form of obtaining legal protection in obtaining better civil rights, political rights, economic rights, social rights and cultural rights. So that when the child becomes an adult, he will understand and understand more about the rights he has. According to Hans Kelsen, legal theory is the science of applicable law and not only of what law should be. The formulation of the problem includes: 1. How is the protection of legal protection for the rights of children who are victims of sexual harassment in laws and regulations? and 2. How is the implementation of legal protection for child victims of sexual harassment in fulfilling the elements of justice? This type of normative research uses a juridical approach, legal principles and comparative law, judging from its nature this research is classified as descriptive research, namely research that describes what is about a situation. The research method used is qualitative with a normative approach. The authors collect data from libraries, documentation, print media and electronic media. From the research results, it can be obtained that legal protection for child victims of sexual harassment is regulated in Law no. 35 of 2014 changes to Law no. 23 of 2002 concerning Child Protection by providing children's rights in terms of access to fulfillment of rights, child victims of sexual abuse get legal protection in terms of providing legal assistance, rehabilitation and prevention, implementation of legal protection for child victims of sexual harassment to obtain their rights and get maximum legal protection and assistance.